Enhancing Students' Creativity and Critical Thinking Through English Competitions in Bulan Bahasa dan Sastra Event - Ita Apriliya; Nurhajati, Diani; Susanti, Yunik (Journal of Development Research, 2024)
School graduates required two essential skills in twenty first century, namely creativity and critical thinking skills. There are many strategies that can be used to develop these skills at schools. One of them is through English competitions. The aims of this research are 1) to describe kinds of English competitions in Bulan Bahasa dan Sastra event that can develop creativity and critical thinking skills; and 2) to explain the process of acquiring creativity and critical thinking skills experienced by students. This qualitative research was carried out at SMAN 2 Kediri. The subjects of this research were six students who took parts in the English competitions, and the teachers who were in charge of as judges in the English competition. The techniques of data collection were observation, interview, and document analysis. The results of research showed that there were two English competitions, namely Speech Contest and English Debate in Bulan Bahasa event. In each of competitions, the students followed the stages: preparation and presentation. Through these stages, the students had experience to develop creativity and critical thinking skills. The researcher concludes that students’ creativity and critical thinking skills can be developed when they are involved in an English competition.